Utilization and Evaluation of Virtual Reality and Simulations in Teaching-Learning Direct Current Circuits - Sinolinding, Kashmera A.; Dionela, Christine Mae; Paez, Jessel James; Arca, John Paul; Apellanes, Rustria; Lamputi, April Joy; Butalid, Smyrth; Bedano, Yvonne; Sales, Roevela Ren; Mercado, Justine C. (Scientechno: Journal of Science and Technology, 2025)
This study evaluates the effectiveness of integrating Virtual Reality (VR) and simulation in teaching direct current (DC) circuits. VR and simulation provide interactive spaces for students to learn, manipulate components, and conduct experiments, thereby enhancing motivation and engagement. The study employs a quasi-experimental design with control and experimental groups. The participants were assessed through pretests and posttests. Pretest results of both groups reveals no significant difference which suggests similar baseline abilities and level of knowledge in relation to DC circuits. The pretest and posttest results showed a significant difference which suggest that after the intervention, both groups showed a significant improvement in their knowledge of Direct Current Circuits. However, posttest results also showed a marked improvement of the experimental group using VR and simulation compared to the control group, supporting the effectiveness of integrating VR and simulation in teaching DC circuits. This suggests that VR and simulation can be valuable resources in instructional delivery, facilitating a deeper understanding and mastery of electrical concepts.